Pengaruh Diklat Santri Siap Guna terhadap Peserta Pelatihan - Darmawan, Dadan (Journal of Nonformal Education and Community Empowerment, 2017)
The purpose of the study analyzed the influence of education and training of students ready for the performance, work motivation, productivity, and competence of trainees. The method used in this research is descriptive quantitative method. Primary data were obtained using questionnaire, while secondary data was through interview and documentation. Research respondents consist of managers and participants who have passed the training. The results showed that 80.83% of participants who belong to the category strongly agreed, argued strongly agree that the training effect on participants who carried out in daily life. Measured by 4 indicators, among them is the performance of 19.67%, motivation of 16.17%, productivity of 15.41% and competence reached 80.64%.